A Fabry-Pérot cavity coupled surface plasmon photodiode for electrical biomolecular sensing - Giles Allison (Nature Portfolio, 2021)
Surface plasmon resonance is well established for biosensing applications, but commonly limited by complex optical detection. Here, the authors present a plasmonic sensor integrated in a photovoltaic cell, which generates an electronic signal sensitive to the solution refractive index via plasmon interaction